Identiteit en Relevansie Die Dringende Noodsaak van Christelike Organisasies en Instellings in ’n Toenemend Sekulêre Suid-Afrika - van der Walt, B. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2003)
The aim of this article is to determine how Christians can, especially by way of Christian organizations, be relevant to our contemporary, secular society without the danger of losing their Christian identity. To answer this question attention is given to the following: (1) the phenomenon and the challenge of secularism; (2) different ways (by individuals, churches and by way of Christian organizations) to respond to the challenge; (3) wrong motives for the establishment and/or maintaining of Christian organizations; (4) the correct motives for doing so; (5) the different categories of Christian organizations and institutions and (6) some concluding remarks.